Energy efficiency analysis as a function of the working voltages in supercapacitors. (1st September 2021) - Quintana, Jose J.; Ramos, Alejandro; Diaz, Moises; Nuez, Ignacio
Abstract: Supercapacitors are increasingly used as energy storage elements. Unlike batteries, their state of charge has a considerable influence on their voltage in normal operation, allowing them to work from zero to their maximum voltage. In this work, a theoretical and practical analysis is proposed of the energy efficiency of these devices according to their working voltages. To this end, several supercapacitors were subjected to charge and discharge cycles until the measurements of current and voltage stabilized. At this point their energy efficiency was calculated. These charge-discharge cycles were carried out: i) without rest between charging and discharging; and ii) with a rest of several minutes between the two stages. Using the information obtained from the tests, the energy efficiency is shown plotted against the minimum and maximum working voltages. By consulting the data and the graphs, the ideal working voltages to optimize the energy efficiency of these devices can be obtained. Highlights: Working voltages affect the energy efficiency of a supercapacitor. Rest periods decrease the energy efficiency in supercapacitors. Charge-discharge cycles method is used to calculate energy efficiency.